2009
DOI: 10.1002/ffj.1941
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of the essential oil of Ferulago campestris (Besser) Grecescu growing in central Italy

Abstract: Essential oil from the fl owers and leaves of Ferulago campestris (Apiaceae) from two collection sites in central Italy was analysed by GC-FID and GC-MS and 134 constituents were identifi ed and quantifi ed by calculating the response factors of FID. Monoterpene hydrocarbons constituted the main fraction of the fl ower oils, with a-pinene, myrcene and g-terpinene as the major components. Sesquiterpenes gave the major contribution to the essential oils from the leaves, with the oxygenated components more abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Viridene 20 has been reported to be present in the essential oils from the Apiaceae family plants such as, Ligusticum grayi 41 , Ligusticum mutellina 42 , and Meum athamanticum 43 . γ-Vetivenene 79 also has been reported to be present in the essential oil from Vetiveria zizanioides 44 , Vetiveria nigritana 45 , and Ferulago campestris 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Viridene 20 has been reported to be present in the essential oils from the Apiaceae family plants such as, Ligusticum grayi 41 , Ligusticum mutellina 42 , and Meum athamanticum 43 . γ-Vetivenene 79 also has been reported to be present in the essential oil from Vetiveria zizanioides 44 , Vetiveria nigritana 45 , and Ferulago campestris 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In this subject, the interest of scientific community is shown on a great number of articles published in which are reported techniques such as microwave‐assisted solvent extraction (MASE) 3, 4, microwave‐assisted hydrodistillation (MAHD) 4–6, solvent‐free microwave extraction (SFME) 7–10, vacuum microwave (VM) 11, 12, compressed air microwave distillation (CAMD) 13, microwave‐accelerated steam distillation (MASD) 14, microwave hydro‐diffusion and gravity (MHG) 15, 16 and finally microwave steam distillation (MSD) 17. However, the composition and consequently the properties of the essential oils extracted through these or conventional methods have been found to vary depending on the method used 9, 10, 16, 18, as well as the aspect linked to the territory 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies on F. campestris revealed the presence of monoterpene coumarins 22; moreover, the composition of the essential oil from a plant growing wild in Turkey was investigated 20. Recently, Maggi et al 19 reported the chemical composition of essential oils obtained by classic hydrodistillation (HD) methods from flowers and leaves of F. campestris collected in two sites in central Italy. The results showed relevant differences compared with the chemical composition reported previously 20.…”
Section: Introductionmentioning
confidence: 99%
“…Among monoterpenoids, bornyl acetate (4.6%) and α-pinene (2.9%) were the most representative compounds. The presence of aromatic aldehydes, such as 2,3,6-trimethyl benzaldehyde, is considered a hallmark of several Ferulago species [ 18 , 19 , 20 , 21 , 22 , 23 ]. It is worth mentioning that these compounds are formed during distillation from the cleavage and molecular rearrangement of ferulol-type monoterpenoids [ 19 ].…”
Section: Resultsmentioning
confidence: 99%